Pengaruh Stigma terhadap Tingkat Kepatuhan Terapi pada Pasien Tuberkulosis: Tinjauan Literatur - Siti Kalila Ramadhani; Elyona Ganis Azka Safuha; Jef Gishard Kristo Kalalo (Poltekkes Kemenkes Padang, 2026)
Tuberculosis (TB) remains a global public health problem, with treatment adherence serving as a key determinant of therapeutic success. One of the main barriers to adherence is social stigma experienced by patients, whether from family members, the community, or the workplace. This study aimed to examine the influence of stigma on treatment adherence among tuberculosis patients based on recent scientific evidence. A systematic literature review was conducted using the Google Scholar and PubMed databases for articles published between 2020 and 2025. A total of 1,076 articles were initially identified. After applying the PICO framework and strict inclusion–exclusion criteria, 200 articles were screened for further assessment, and 9 eligible studies were ultimately selected and analyzed narratively. The review findings consistently demonstrated a significant negative association between stigma and TB treatment adherence (p < 0.05). Stigma affects adherence directly through feelings of shame and social isolation, and indirectly through depression and psychological distress. In conclusion, social stigma represents a universal and multidimensional barrier to TB treatment adherence; therefore, TB control interventions should integrate psychosocial approaches alongside medical management.